Early career academics navigating the ecology of the university: a collaborative autoethnography - Andrew Doyle; Janina Suppers; Emma Cunningham; Brent Wagner (Kōtuitui)
Early career academics (ECAs) are negatively affected by the neoliberal university which encourages performativity, competition and a ‘publish or perish’ mentality. In this paper a group of four ECAs in the Aotearoa New Zealand context explore and navigate the neoliberal university through a collaborative autoethnography. Collectively, we adopt Barnett’s [2018. The ecological university: A feasible utopia. Routledge, Taylor & Francis Group.] five dimensions of ecologies framework to study our own experiences. Findings suggest that as ECAs, we seek connection to academia, experience workload and power imbalance, and actively learn how to navigate roles. We also describe how our research group created a supportive environment within the competitive space of academia that fostered feelings of belonging and offered support in navigating the university ecology. Furthermore, working in initial teacher education, as a high service discipline, created unique challenges for us such as high service and teaching roles which may negatively impact ECAs. Through this lens of initial teacher education, we in turn make recommendations for universities to better support early career academics.